Die Prototypensemantik als Möglichkeit der fremdsprachen- didaktischen Lexikographie.: Ein Vorschlag der prototypenbasierten Bedeutungsbeschreibung für kulturbasierte Wörterbucheinträge - Pichler , Anna Malena (Linguistik Online, 2021)
It has often been criticized that Learners’ Dictionaries lack a theoretical basis in linguistic theory. Prototype semantics are able to provide a solution to this problem in the context of cognitive linguistics. This article proposes a new approach to pedagogical lexicography based on the fundamental ideas of prototype semantics. In the framework of a culture-based dictionary for German as a Foreign Language (Kulturwörterbuch Deutsch als Fremdsprache), which is implemented as a students’ project at the department for German as a Foreign Language of TU Berlin, the model of a prototype-based semantic explanation is presented.